Two Feet on the Ground: Standing Proud - Australian Government, Department of Families, Housing, Community Services and Indigenous Affairs (My University, 2010)
This booklet is the second in a series of books that gives feedback to the community about Footprints in Time, the Longitudinal Study of Indigenous Children (LSIC), undertaken by the Australian Government Department of Families, Housing, Community Services and Indigenous Affairs (FaHCSIA). The first booklet Finding our feet gave the results from the first wave, or first interviews, of the study, while this booklet Two feet on the ground – standing proud looks at results from the second round of interviews.
Keywords: Culture -- Indigenous; Culture; Culture and language; Culture; Indigenous; Culture and identity; Culture, identity and language